2014
DOI: 10.1038/ncomms4522
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of two-dimensional oxide-interfacial charges into one-dimensional electron chains by the misfit-dislocation strain field

Abstract: The success of semiconductor technology is largely ascribed to controlled impacts of strains and defects on the two-dimensional interfacial charges. Interfacial charges also appear in oxide heterojunctions such as LaAlO 3 /SrTiO 3 and (Nd 0.35 Sr 0.65 )MnO 3 /SrTiO 3 . How the localized strain field of one-dimensional misfit dislocations, defects resulting from the intrinsic misfit strains, would affect the extended oxide-interfacial charges is intriguing and remains unresolved. Here we show the atomic-scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 43 publications
(116 reference statements)
2
37
1
Order By: Relevance
“…This result suggested that the dislocation array could have influence on the electronic defect level distribution in the bandgap. Recently, the condensation of two-dimensional oxide-interfacial charges into one-dimensional electron chains by the misfit-dislocation strain field was reported [18]. Our STM image has responded their results that the dislocation line can be revealed by the scanning tunneling current with higher charge density condensed on the dislocation array.…”
Section: Resultssupporting
confidence: 69%
“…This result suggested that the dislocation array could have influence on the electronic defect level distribution in the bandgap. Recently, the condensation of two-dimensional oxide-interfacial charges into one-dimensional electron chains by the misfit-dislocation strain field was reported [18]. Our STM image has responded their results that the dislocation line can be revealed by the scanning tunneling current with higher charge density condensed on the dislocation array.…”
Section: Resultssupporting
confidence: 69%
“…The lattice mismatch can be accommodated as elastic strain or as a combination of elastic and plastic strain. A high density of dislocations (two orders higher than those in bulk) can be found at the interface of thin films [6][7][8] upon relaxation of elastic strain. This high density of dislocations makes the study of their effect on the properties of the material of paramount importance.…”
mentioning
confidence: 97%
“…Generally, in contrast with the bulk, thin films are not only the existing status for many materials in devices, but they also promise many novel properties due to the unique structural features1112131415. For example, misfit dislocations (MDs) are commonly observed in thin films while one dimensional electron chains are found at these MDs in magnetic thin films11.…”
mentioning
confidence: 99%
“…For example, misfit dislocations (MDs) are commonly observed in thin films while one dimensional electron chains are found at these MDs in magnetic thin films11. And interfaces, such as film/substrate interfaces, twins or stacking faults, can provide another degree of freedom to mediate the property of thin films, where superconductivity13, ferroelectricity14, and novel magnetic phase15 can be generated.…”
mentioning
confidence: 99%